Corinthian capitals from the Hellespontus - Ayşe Çaylak Türker (Polish Archaeology in the Mediterranean, 2023)
The Hellespont area, owing to its key geographical location, played a dominant role in production, consumption, as well as trade contacts between the Black Sea and the Mediterranean during the Byzantine period. Despite the importance of this region, archaeological data from it is rather limited, hindering research on the history of the Hellespont in the Byzantine period. Archaeological surveys have been conducted in the valleys of the Hellespont catchment area in order to determine the location of Byzantine villages and to understand regional settlement patterns. An important group of objects identified as a result of this fieldwork were architectural members. The finds included numerous column capitals and fragments of liturgical furnishings. The present study examines Corinthian capitals, which constitute the most frequently occurring type of column capital, numbering 30 documented examples. All specimens were made from white or gray-veined white Prokonnesian marble. The general aims of research on this material are, firstly, to understand the nature of the now-lost buildings they came from, and, secondly, to contribute information on the location of settlements in the region. The specimens under consideration were identified during field surveys in Çanakkale, as well as during a query in the Çanakkale Archaeology Museum.